La destruction séléctive des lieux par les « hooligans » de Belgrade - Amaël Cattaruzza (EchoGéo)
The Kosovo’s independency proclaimed on the 17th February 2008 was immediately followed by violent reactions of young “hooligans” in Belgrade. Their selective destructions of places revealed a clear message against countries which planed to recognize this secession. This crisis context produced a brutal shift of the symbolical geography and of the daily experience of places in the town.